From discursive event to discourse événement: A case study of political-religious discourse in Argentina - Bonnin, Juan Eduardo (2011)
This article analyses the interplay between religious and political discourse in Argentina, departing from a case study located in the transition towards democracy in April 1987, and conveying military, political and religious discourse within the conflicts that surrounded the government of President Raúl R. Alfonsín (1983–1989). It involved a well-established discourse genre, the homily, within an historical social practice, the Catholic mass; but it also included the violation of one of its main features, namely the monopoly of talk by priests. By challenging the bishop’s monologue, questioned by the homily, President Alfonsín settled a different ground, neither religious nor political, an événement that required urgent recontextualization. The mass media, as privileged agents representing contemporary social practices, recontextualized it through the multimodal attribution of "genericity" (Adam and Heidmann, 2004) in two main different ways, ascribing the event to either a religious or political field. In both cases, as we will see later, the actions and actors involved were consistently opposite, responding to different ideological motivations and with different strategic goals. The underlying theoretical point is that genres are not fixed in events, but rather represent ways of dealing with the exceptionality of événements that bring out ideological or political tensions.